Ce-Zr composite oxide, method for producing the same, and exhaust gas purification catalyst using the same
By using Ce-Zr composite oxides with small crystalline diameter and high BET specific surface area, the problem of low oxygen release performance at low temperatures in the prior art is solved, and more efficient exhaust gas purification performance is achieved.
Patent Information
- Application Number
- CN202180017582.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-28
- Filing Date
- 2021-04-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2041-04-05
AI Technical Summary
The existing ceria-zirconia solid solution has low oxygen release performance at low temperatures, resulting in insufficient exhaust gas purification capacity.
Ce-Zr composite oxide with a microcrystal diameter of less than 6.5 nm and a BET specific surface area of more than 90 m2/g was used as the oxygen storage material, and the oxygen absorption and release performance were improved by solvothermal method and surface stabilization treatment.
Releasing oxygen at lower temperatures than before significantly improving exhaust gas purification performance at low temperatures, especially excellent purification effects on carbon monoxide (CO), hydrocarbons (HC) and nitrogen oxides (NOx).
Smart Images

Figure GDA0003819811380000031 
Figure GDA0003819811380000271 
Figure HDA0003819811320000011
Abstract
Description
Technical Field
[0001] The present invention relates to a Ce-Zr composite oxide, a method for producing the same, and an exhaust gas purification catalyst using the same. Background Art
[0002] In recent years, automobile exhaust gas control has become increasingly stringent. In order to cope with the intensification of control, it is sought to further improve the exhaust gas purification performance of exhaust gas purification catalysts. In particular, since it is difficult to reduce nitrogen oxides (NOx) while oxidizing carbon monoxide (CO) and hydrocarbons (HC), technologies for improving NOx purification performance are being actively developed.
[0003] As a method for purifying NOx, there are two methods, one in which NOx is directly decomposed into nitrogen (N2) and the other in which NOx is reacted with a reducing agent to be reduced into N2. However, the former direct decomposition method is extremely difficult, and therefore the latter method using a reducing agent is currently widely used.
[0004] The method of using an oxygen storage material to purify NOx is effective. For example, it is reported that zirconia powder in which ceria is solid-dissolved (ceria-zirconia solid solution) is used as an oxygen storage material (Japanese Patent Publication No. 10-212122). The ceria-zirconia solid solution described in Japanese Patent Publication No. 10-212122 has a high surface area, and therefore, the amount of oxygen absorbed and released increases (Example). Summary of the invention
[0005] However, the average particle size of the ceria-zirconia solid solution disclosed in Japanese Patent Publication No. 10-212122 is as large as 0.01 μm (10 nm) or more. This ceria-zirconia solid solution has low oxygen release performance, especially at low temperatures. Therefore, when this ceria-zirconia solid solution is used as an exhaust gas purification catalyst, the exhaust gas purification capacity, especially at low temperatures, is insufficient.
[0006] Therefore, the present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a means for releasing oxygen at a lower temperature than conventional methods.
[0007] Another object of the present invention is to provide means for improving exhaust gas purification performance, particularly exhaust gas purification performance at low temperatures.
[0008] The ceria-zirconia composite oxide (Ce-Zr composite oxide) according to one embodiment of the present invention has a crystallite diameter of 6.5 nm or less and a BET specific surface area of 90 m 2 / g or above. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1This is a graph showing the BET specific surface areas of powders A to G.
[0010] Figure 2 This is a graph showing the BET specific surface areas of powders H and I.
[0011] Figure 3 This is a graph showing the BET specific surface areas of powders J and K.
[0012] Figure 4 This is a graph showing the relationship between the peak temperature in H2-TPR measurement and the R value.
[0013] Figure 5 It is a graph showing the exhaust gas purification performance results of exhaust gas purification catalysts M and N. DETAILED DESCRIPTION
[0014] The following describes the embodiments of the present invention, but the scope of protection of the present invention should be determined according to the description of the claims and is not limited to the following embodiments. It should be noted that the numerical range "A to B" in this specification includes A and B, which means "above A and below B". In addition, "A and / or B" means "either A or B" or "both A and B".
[0015] The Ce-Zr composite oxide according to one embodiment of the present invention has a crystallite diameter of 6.5 nm or less and a BET specific surface area of 90 m 2 / g or more. The Ce-Zr composite oxide of this structure can release oxygen at a lower temperature than before. Therefore, according to the catalyst obtained by using the Ce-Zr composite oxide of the present invention, the exhaust gas purification ability is improved.
[0016] The inventors of the present invention have conducted intensive research on the problems to be solved by the present invention. As a result, it was found that the maximum crystallite diameter is as small as 6.5 nm and the BET specific surface area is as large as 90 m 2 A composite containing Ce and Zr (Ce-Zr composite; hereinafter also referred to as "composite") with an average mass of 1000 t / g or more can absorb and release oxygen at lower temperatures than ever before, and a catalyst containing such a Ce-Zr composite oxide has excellent exhaust gas purification performance at low temperatures.
[0017] The reason why the Ce-Zr composite oxide according to the present invention improves the exhaust gas purification performance at low temperatures by having the above-mentioned structure is not yet clear, but the present inventors speculate as follows. It should be noted that the present invention is not limited to the following mechanism.
[0018] The Ce-Zr composite oxide has small microcrystals and a high specific surface area. Therefore, when compared with the conventional Ce-Zr composite oxide with large microcrystals and a low specific surface area, the exposed areas of cerium dioxide and zirconium oxide are large. Therefore, when this Ce-Zr composite oxide comes into contact with exhaust gas, the probability of contact with the exhaust gas can be increased. Therefore, it can be considered that the reaction rate of the following formula (1) based on the Ce-Zr composite oxide is increased, and its oxygen storage and release characteristics are excellent even at low temperatures.
[0019] Formula (1):
[0020]
[0021] In the reaction of the above formula (1), the reduction reaction of CeO2 occurs by contacting with reducing agents such as carbon monoxide (CO) and hydrocarbons (HC). Therefore, the Ce-Zr composite oxide with an increased probability of contact with gases such as CO and HC has a high oxygen release ability even at low temperatures, and has excellent exhaust gas purification performance including carbon monoxide (CO) and hydrocarbons (HC).
[0022] <Ce-Zr composite oxide>
[0023] The Ce-Zr composite oxide described in the present invention contains a metal and / or metal oxide of Ce and a metal and / or metal oxide of Zr. The Ce-Zr composite oxide described in the present invention stores oxygen in an oxidizing atmosphere (lean) and releases oxygen in a reducing atmosphere (rich) according to the change in the air-fuel ratio (A / F) that changes with the operating conditions, and thus functions as an oxygen storage material (also referred to as "oxygen storage and release substance") that enables the oxidation / reduction reaction to proceed stably.
[0024] (Microcrystal diameter)
[0025] The Ce-Zr composite oxide described in the present invention has a crystallite diameter of less than 6.5nm. Here, if the crystallite diameter exceeds 6.5nm, the storage / release performance of oxygen is low. In addition, it is difficult or impossible to release oxygen at low temperatures (therefore, the purification performance of exhaust gas (especially CO, HC) at low temperatures is poor). From the viewpoint of further improving the effect of oxygen release performance at low temperatures (the purification performance of exhaust gas (especially CO, HC) at low temperatures), the crystallite diameter of the Ce-Zr composite oxide is preferably less than 6.5nm, more preferably less than 5.5nm, and particularly preferably less than 4.6nm. It should be noted that the smaller the crystallite diameter of the Ce-Zr composite oxide (the more microcrystalline), the easier it is to release lattice oxygen inside the lattice, and the oxygen storage and release characteristics derived from cerium can be fully utilized. In addition, the smaller the crystallite diameter, the easier it is for oxygen to be conducted, so it is preferred. It should be noted that oxygen conduction refers to the following phenomenon. That is, when the gas atmosphere of the exhaust gas changes from deficiency to abundance or from abundance to deficiency, the oxygen conduction phenomenon occurs between the surface and the interior of the Ce-Zr composite oxide particles. When the exhaust gas atmosphere changes from deficiency to abundance, the oxygen adsorbed by Ce (referred to as Ce0) near the surface is easily released. Then, the oxygen held by Ce (referred to as Ce1) adjacent to Ce0 that has released the oxygen and closer to the interior of the crystal moves to Ce0 and conducts. Similarly, by being continuous with Ce2, Ce3, and Ce4, it is possible for oxygen conduction to occur continuously from the interior of the crystal. In addition, when the gas atmosphere of the exhaust gas changes from abundance to deficiency, on the contrary, the oxygen in the gas phase is first adsorbed on Ce0, and the adjacent Ce1 will rob Ce0 of oxygen, thereby allowing Ce0 to adsorb other oxygen. The oxygen held by Ce1 is further robbed by Ce2 closer to the interior, thereby continuously conducting oxygen from the surface to the interior.
[0026] Ce-Zr composite oxides with large crystallite diameters require time for the conduction of oxygen deep inside them, so it is difficult for oxygen to be released at low temperatures. Therefore, the lower limit of the crystallite diameter is not particularly limited, and is preferably greater than 1.0 nm, more preferably greater than 2.0 nm, further preferably greater than 3.0 nm, and particularly preferably greater than 3.0 nm. That is, the Ce-Zr composite oxides described in the present invention have a crystallite diameter that is preferably greater than 1.0 nm and less than 6.5 nm, more preferably greater than 2.0 nm and less than 6.5 nm, further preferably greater than 3.0 nm and less than 5.5 nm, and particularly preferably greater than 3.0 nm and less than 4.6 nm.
[0027] The crystallite diameter of the Ce-Zr composite oxide can be measured by a known method such as an X-ray diffraction method, a TEM method, etc. In addition, in this specification, the crystallite diameter of the Ce-Zr composite oxide is a value measured by the following method.
[0028] In the diffraction pattern of XRD (X-ray diffraction), the measurement result of the peak at 2θ=28 to 30° was substituted into the following Scherrer equation to calculate the crystallite diameter of the Ce—Zr composite oxide.
[0029] [Mathematical formula 1]
[0030] Scherrer's formula:
[0031] Crystallite diameter (nm) = K × λ / βcosθ
[0032] In the above Scherrer's equation, λ is the wavelength of X-rays (nm), θ is the diffraction angle (°), K is the shape factor (constant), and β is the peak width corrected for the spread of diffraction lines due to the device. The measurement procedure was performed in accordance with JIS H7805:2005.
[0033] (BET specific surface area)
[0034] Based on the above, the Ce-Zr composite oxide of the present invention has a 90m 2 / g or more BET (Brunauer-Emmett-Teller) specific surface area. Here, if the BET specific surface area is less than 90m 2 / g, the exposed area of Ce-Zr is low, the probability of contact with exhaust gas is reduced, and the oxygen storage and release characteristics cannot be fully exerted. In addition, the precious metal cannot be fully dispersed when manufacturing the catalyst. From the viewpoint of further improving the oxygen storage and release characteristics and obtaining sufficiently dispersed precious metals, the BET specific surface area of the Ce-Zr composite oxide of the present invention is preferably 135m 2 / g or more, more preferably 165m 2 / g or more, particularly preferably 180m 2 / g or more. It should be noted that the larger the BET specific surface area of the Ce-Zr composite oxide, the higher the probability of contact with oxygen. Therefore, the upper limit of the BET specific surface area is not particularly limited, but is usually 470 m 2 / g or less. If the BET specific surface area exceeds 470m 2 / g, the viscosity of the slurry becomes high, making it difficult to prepare the catalyst, which is not preferred. The BET specific surface area of the Ce-Zr composite oxide of the present invention is preferably 320 m 2 / g or less. That is, the Ce-Zr composite oxide of the present invention preferably has a 2 / g and above 470m 2 / g or less, more preferably 135m 2 / g and above 320m 2 / g or less, more preferably 165m 2 / g and above 320m 2 / g or less, particularly preferably 180m 2 / g and above 320m 2 / g or less BET specific surface area.
[0035] In this specification, the BET specific surface area of the Ce-Zr composite oxide is a value measured by the BET method using nitrogen as an adsorbed molecule. Specifically, the BET specific surface area (m 2 / g). In addition, the BET specific surface area of the Ce-Zr composite oxide is the BET specific surface area of the Ce-Zr composite oxide as a final product, and is the "BET specific surface area (after structure stabilization treatment)" in the following Examples.
[0036] (R value)
[0037] The Ce-Zr composite oxide of the present invention preferably has a small crystallite diameter of less than 6.5 nm and a diameter of 90 nm. 2 / g or more high BET specific surface area, and has the following relationship. Even if the BET specific surface area is large but the crystallite diameter is large, or even if the crystallite diameter is small but the BET specific surface area is small, the Ce-Zr composite oxide will not fully release oxygen at low temperatures. Due to the turbulent diffusion of oxygen molecules originating from the high surface area, the oxygen molecules will reach a large amount of Ce-Zr composite oxide, and by having a specified crystallite diameter, the lattice oxygen inside the crystal can easily be separated from the lattice. It is found here that the value obtained by dividing the BET specific surface area of the Ce-Zr composite oxide by the surface area calculated from the crystallite diameter (=S / (πr 2 )(S = BET specific surface area (m 2 / g), r=crystallite diameter (nm)); also called "R value") is within the specified range, the oxygen storage and release characteristics can be further improved. Specifically, the Ce-Zr composite oxide has an R value that is preferably greater than 1.5, more preferably greater than 1.5 and less than 30, further preferably greater than 2.0 and less than 8.0, and particularly preferably greater than 2.5 and less than 6.6. Among Ce-Zr composite oxides having such an R value, Ce-Zr composite oxides with small crystallite diameters do not aggregate and have a high surface area. As a result, the movement of lattice oxygen inside the crystal (oxygen conduction) is easy to occur even at low temperatures, and high oxygen storage and release characteristics can be exerted (therefore, exhaust gas purification performance at lower temperatures can be exerted).
[0038] The Ce-Zr composite oxide described in the present invention must contain metal and / or metal oxide of Ce (preferably metal oxide of Ce (ceria)), and metal and / or metal oxide of Zr (preferably metal oxide of Zr (zirconium oxide)). Here, the ratio of cerium (Ce) in the Ce-Zr composite oxide is preferably 5 to 80% by mass, more preferably 20 to 70% by mass, relative to the Ce-Zr composite oxide in terms of CeO2. If it is within this range, oxygen in the exhaust gas can be stored. In addition, the ratio of zirconium (Zr) in the Ce-Zr composite oxide is preferably 20 to 95% by mass, more preferably 30 to 80% by mass, relative to the Ce-Zr composite oxide in terms of ZrO2. If it is within this range, the oxygen stored in Ce can be released efficiently.
[0039] The Ce-Zr composite oxide of the present invention may further contain metal elements other than Ce and Zr (hereinafter also referred to as "other metal elements") as needed. As other metal elements, neodymium (Nd), lanthanum (La), praseodymium (Pr) and yttrium (Y) can be listed. Among these, it is preferred to contain at least one of Nd, La and Y, more preferably to contain La or Y, and particularly preferably to contain La. Here, the above-mentioned other metal atoms may exist in the form of metal and / or metal oxide, preferably in the form of metal oxide. That is, in a preferred form of the present invention, the Ce-Zr composite oxide of the present invention is composed of at least one selected from cerium and ceria and at least one selected from zirconium and zirconium oxide, or, it is composed of at least one selected from cerium and ceria, at least one selected from zirconium and zirconium oxide, and at least one metal selected from the group consisting of neodymium, lanthanum, praseodymium and yttrium or the oxide of the aforementioned metal. It should be noted that in the above description, "consisting of..." includes "consisting only of..." and "consisting essentially of...". “Consisting of…” preferably means “consisting only of…” It should be noted that in this specification, “substantially” means that components other than the specified components are contained in a ratio of less than 0.5 atomic % (lower limit: 0 atomic %) relative to the total atomic number of metal elements contained in the Ce-Zr composite oxide.
[0040] When the Ce-Zr composite oxide of the present invention further contains neodymium (Nd), the ratio of neodymium (Nd) in the Ce-Zr composite oxide is preferably more than 0% by mass and less than 15% by mass, and more preferably 2 to 10% by mass, relative to the Ce-Zr composite oxide in terms of Nd2O3. If it is within this range, a sufficient ratio of the number of atoms of Ce and Zr can be ensured, and therefore, excellent oxygen storage and release characteristics can be achieved.
[0041] When the Ce-Zr composite oxide of the present invention further contains lanthanum (La), the ratio of lanthanum (La) in the Ce-Zr composite oxide is preferably more than 0% by mass and less than 15% by mass, and more preferably 2 to 10% by mass, relative to the Ce-Zr composite oxide in terms of La2O3. If it is within this range, a sufficient ratio of the number of atoms of Ce and Zr can be ensured, and therefore, excellent oxygen storage and release characteristics can be achieved, and in addition, the thermal stability of the Ce-Zr composite oxide can be further improved.
[0042] When the Ce-Zr composite oxide of the present invention further contains praseodymium (Pr), the ratio of praseodymium (Pr) in the Ce-Zr composite oxide is preferably more than 0% by mass and less than 15% by mass, and more preferably 2 to 10% by mass, relative to the Ce-Zr composite oxide in terms of Pr2O3. If it is within this range, a sufficient ratio of the number of atoms of Ce and Zr can be ensured, and therefore, excellent oxygen storage and release characteristics can be achieved.
[0043] When the Ce-Zr composite oxide of the present invention further contains yttrium (Y), the ratio of yttrium (Y) in the Ce-Zr composite oxide relative to the total atomic number of metal elements contained in the Ce-Zr composite oxide is preferably more than 0 mass % and less than 15 mass %, and more preferably more than 0 mass % and less than 10 mass %, in terms of Y2O3. If it is within this range, a sufficient ratio of the atomic number of Ce and Zr can be ensured, and therefore, excellent oxygen storage and release characteristics can be achieved.
[0044] In addition, in this specification, the content rate (mass %) of each element in a composite body is calculated from the result of XRF analysis by the following method.
[0045] (XRF analysis)
[0046] The Ce-Zr composite oxide was crushed by a disc mill and formed into a circular plate with a diameter of 31 mm and a thickness of 5 mm by a press machine as a sample. The sample was subjected to XRF analysis using S8 TIGER (wavelength dispersion type, Rh tube ball) manufactured by BRUKER ANALYTIK. Based on the obtained spectrum, the ratio (atomic %) of the number of atoms of Ce and Zr and other components (neodymium, lanthanum, praseodymium and yttrium) (i.e., all metal elements) was calculated when the total number of atoms was 100%.
[0047] The crystal structure of the Ce-Zr composite oxide is cubic, tetragonal, monoclinic, or rhombic, etc., preferably cubic, tetragonal or monoclinic, and more preferably cubic or tetragonal.
[0048] The Ce-Zr composite oxide of the present invention is manufactured by using a solvothermal method at a specific temperature, and performing a structural stabilization treatment after performing a surface stabilization treatment. Specifically, a cerium compound, a zirconium compound, and a compound containing at least one metal selected from the group consisting of neodymium, lanthanum, praseodymium, and yttrium as required are mixed to obtain a mixture; the mixture is subjected to a solvothermal treatment at a temperature exceeding 250°C to obtain a solvothermal treatment product; the solvothermal treatment product is subjected to a surface stabilization treatment at a temperature above 220°C and below 380°C to obtain a precursor; the precursor is subjected to a structural stabilization treatment at a temperature above 380°C to generate a Ce-Zr composite oxide.
[0049] That is, in another embodiment of the present invention, a method for producing a Ce-Zr composite oxide is provided, which comprises the following steps: mixing a cerium compound and a zirconium compound to obtain a mixture; subjecting the aforementioned mixture to a solvent thermal treatment at a temperature exceeding 250°C to obtain a solvent thermal treatment product; subjecting the aforementioned solvent thermal treatment product to a surface stabilization treatment at a temperature above 220°C and below 380°C to obtain a precursor; and subjecting the aforementioned precursor to a structural stabilization treatment at a temperature above 380°C to generate a Ce-Zr composite oxide.
[0050] In addition, in other embodiments of the present invention, a method for producing a Ce-Zr composite oxide is provided, which has the following steps: mixing a cerium compound, a zirconium compound, and a compound containing at least one metal selected from the group consisting of neodymium, lanthanum, praseodymium and yttrium to obtain a mixture; subjecting the aforementioned mixture to a solvent thermal treatment at a temperature exceeding 250°C to obtain a solvent thermal treatment product; subjecting the aforementioned solvent thermal treatment product to a surface stabilization treatment at a temperature above 220°C and below 380°C to obtain a precursor; and subjecting the aforementioned precursor to a structural stabilization treatment at a temperature above 380°C to generate a Ce-Zr composite oxide.
[0051] Hereinafter, each step will be described in sequence. It should be noted that the method described in the other embodiment and another embodiment differs only in whether the Ce-Zr composite oxide contains other metal elements. Therefore, the overlapping matters will be described together in the following.
[0052] (Step (I))
[0053] First, a cerium compound as a Ce raw material, a zirconium compound as a Zr raw material, and, if necessary, other metal raw materials as other metal element raw materials are preferably mixed in a solvent (step (I)).
[0054] Here, the cerium compound is not particularly limited, and is preferably dissolved in a solvent. Specifically, halides such as cerium chloride, inorganic salts such as cerium nitrate and cerium sulfate, carboxylates such as cerium acetate and cerium (III) 2-ethylhexanoate, cerium hydroxide, and complex compounds (such as cerium triacetylacetonate (III)) obtained by coordinating ligands such as acetylacetone and alkoxides (methoxide, ethanolate, tert-butoxide, etc.) on cerium. Among these, cerium nitrate and cerium triacetylacetonate (III) are preferred. These cerium compounds can be used alone or in combination of two or more. In addition, these cerium compounds can be in the form of hydrates. The amount of cerium compound added is not particularly limited, and is preferably an amount that reaches the ratio of the number of atoms of Ce in the above-mentioned Ce-Zr composite oxide. In addition, these cerium compounds can use synthetic products, or commercial products can also be used.
[0055] The above-mentioned zirconium compound is not particularly limited, and is preferably dissolved in a solvent. Specifically, halides such as zirconium chloride (IV), zirconium chloride (III), zirconium oxychloride, and dialkoxy zirconium dichloride can be listed; inorganic salts such as zirconium nitrate, zirconium oxynitrate, zirconium sulfate, and zirconium oxysulfate; carboxylates such as zirconium acetate and 2-ethylhexanoate; zirconium hydroxide; tetraalkoxy zirconiums such as zirconium tetra-n-propoxide, zirconium tetraisopropoxide, zirconium tetraethanol, and zirconium tetra-n-butoxide; complex compounds obtained by coordinating ligands such as acetylacetone and alkoxides (methoxide, ethanolate, tert-butoxide, etc.) on zirconium (e.g., zirconium acetylacetonate, zirconium tetra(acetylacetone), zirconium tetra(diethylmalonic acid), and zirconium tetra(acetoacetic acid)). Among these, zirconium tetra-n-propoxide and zirconium acetylacetonate are preferred. These zirconium compounds can be used alone or in combination of two or more. In addition, these zirconium compounds can be in the form of hydrates. The amount of the zirconium compound added is not particularly limited, but is preferably an amount that satisfies the ratio of the number of Zr atoms in the Ce-Zr composite oxide. In addition, these zirconium compounds may be synthesized products or commercial products.
[0056] In addition, when the Ce-Zr composite oxide contains other metal elements, the other metal raw materials are not particularly limited, and are preferably dissolved in a solvent. Specifically, inorganic salts such as nitrates (such as lanthanum nitrate, yttrium nitrate) and phosphates (such as lanthanum phosphate) of other metal elements can be listed; halides (such as lanthanum chloride, yttrium chloride) of other metal elements; carboxylates such as acetates (such as lanthanum acetate, yttrium acetate) of other metal elements; hydroxides (such as lanthanum hydroxide, yttrium hydroxide) of other metal elements; complex compounds (such as lanthanum acetylacetonate, yttrium acetylacetonate) obtained by coordinating ligands such as acetylacetone and alkoxides (methoxide, ethanolate, tert-butoxide, etc.) on other metal elements; lanthanum 2-ethylhexanoate, yttrium 2-ethylhexanoate, etc. Among these, complex compounds (such as lanthanum acetylacetonate, yttrium acetylacetonate) obtained by coordinating acetylacetone on other metal elements are preferred, and lanthanum acetylacetonate and yttrium acetylacetonate are more preferred. These other metal raw materials can be used alone or in combination of two or more. In addition, these other metal raw materials can be in the form of hydrates. The amount of other metal raw materials added is not particularly limited, and is preferably an amount that reaches the ratio of the number of atoms of each other metal element in the above-mentioned Ce-Zr composite oxide. In addition, these other metal raw materials can use synthetic products, or commercial products can also be used.
[0057] The mixing ratio of the cerium compound, the zirconium compound, and other metal raw materials is not particularly limited, but is preferably appropriately selected so that the composition of the Ce-Zr composite oxide becomes the above-mentioned composition.
[0058] The solvent is not particularly limited as long as it can dissolve or suspend the cerium compound, the zirconium compound and other metal raw materials when added, and it is preferably able to dissolve them. Specifically, alcohols such as 1,4-butanediol, octanol, and glycerol; alkylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, etc. can be listed. These solvents can be used alone or in combination of two or more. Among these, 1,4-butanediol and octanol are preferred, and 1,4-butanediol is more preferred.
[0059] The amount of solvent used is not particularly limited as long as it can dissolve the above-mentioned cerium compound, zirconium compound and other metal raw materials as needed, and can be subjected to the following solvent heat treatment. Specifically, it is an amount such that the solid content concentration (the total weight of the cerium compound, zirconium compound and other metal raw materials as needed in 100 mL of solvent) reaches 0.01 to 5 g / 100 mL of solvent, preferably an amount such as 0.1 to 3 g / 100 mL of solvent.
[0060] (Step (II))
[0061] For the mixture obtained in the above-mentioned step (I), implement solvent thermal treatment (processing based on solvent thermal method) to obtain solvent thermal treatment product. Here, solvent thermal treatment is carried out in the same operation or suitable modification as the existing known method except reaction (heating) temperature. Solvent thermal treatment is preferably carried out in a closed system (such as in an autoclave). In addition, solvent thermal treatment is preferably carried out in an atmosphere replaced with an inert gas (such as nitrogen, argon, helium, etc.). That is, in a preferred form of the present invention, solvent thermal treatment is carried out in a closed system replaced by an inert gas.
[0062] The reaction temperature in the solvent thermal treatment exceeds 250°C. Here, if the reaction temperature is below 250°C, the solvent is bonded to solutes such as cerium (Ce) and zirconium (Zr) in the form of a ligand, and therefore, due to the mutual repulsion of ligands having the same polarity, the aggregation reaction of Ce and Zr (and, if included, with other metal elements) does not proceed. On the other hand, at a temperature higher than 250°C, the ligand is separated from the solute (Ce, Zr, etc.), and therefore, the aggregation reaction of Ce and Zr (and, if included, with other metal elements) proceeds. Therefore, in the method described in the present invention, when the solvent thermal method is carried out at a temperature higher than 250°C, the crystallite diameter of the final product Ce-Zr composite oxide can be reduced to less than 6.5nm, and the BET specific surface area can be increased to 90m 2 / g or above.
[0063] The above reaction is particularly suitable for the case where 1,4-butanediol is used as a solvent. It should be noted that the above mechanism is a speculation, and the present invention is not limited to the above speculation. From the viewpoint of the aggregation reaction efficiency of Ce and Zr (and other metal elements when included) (therefore, further reduction of crystallite diameter and further increase of BET specific surface area), the reaction temperature in the solvent thermal treatment is preferably above 255°C and below 500°C, more preferably above 270°C and below 400°C, and particularly preferably above 300°C and below 350°C. Solvent thermal treatment conditions other than the above temperature are not particularly limited as long as they are conditions under which Ce and Zr (and other metal elements when included) will undergo an aggregation reaction. The reaction pressure is preferably above 1 MPa and below 30 MPa, more preferably above 5 MPa and below 15 MPa. The reaction time is preferably above 30 minutes and below 15 hours, more preferably above 1 hour and below 4 hours.
[0064] After the solvent thermal treatment, the reaction product (aggregate) is generated as a precipitate. The reaction product (aggregate) is separated by a known method such as centrifugation or filtration.
[0065] (Step (III))
[0066] The solvent heat-treated product obtained in the above step (II) is subjected to a surface stabilization treatment at a temperature of not less than 220°C and not more than 380°C to obtain a precursor. By performing the surface stabilization treatment, it is mainly possible to burn low-temperature combustion organic components (organic components having a boiling point of not less than 220°C and not more than 380°C) in the solvent components other than nitrate ions. In addition, by performing the surface stabilization treatment, an oxide is formed on the surface of the Ce-Zr composite oxide in a state of a crystallite diameter of not more than 6.5nm and is stabilized. If the surface stabilization treatment is not performed and only the later-described structure stabilization treatment is performed, it is difficult to obtain a crystallite having a crystallite diameter of not more than 6.5nm and a diameter of 90nm. 2 / g or more of Ce-Zr composite oxide with a high BET specific surface area. It can be considered that this is because: if only the structural stabilization treatment is performed without surface stabilization treatment, the oxide stabilization of the surface and the combustion of low-temperature burning organic matter, high-temperature burning organic matter (organic components with a boiling point of 380°C or more) and nitrate ions inside will occur simultaneously, so the heat and flame generated during the combustion will also cause the growth of crystals to occur simultaneously. Here, if the surface stabilization treatment temperature is less than 220°C, solvent components above 220°C and below 380°C will remain on the precursor, and these residual solvents will burn in the structural stabilization treatment as a subsequent process. As a result, the crystallite diameter increases in the structural stabilization treatment, so it is not preferred. In addition, if the surface stabilization treatment temperature is above 380°C, not only the solvent components above 220°C and below 380°C, but also the organic components in the raw materials of the catalytic components will burn and release heat at the same time, so it is not preferred. In addition, from the viewpoint of the aggregation reaction efficiency of Ce and Zr (and other metal elements when included) (therefore, further reduction of crystallite diameter and further increase of BET specific surface area), the surface stabilization treatment temperature is preferably above 230°C and less than 370°C, and more preferably above 240°C and less than 350°C. In addition, the time of the surface stabilization treatment is not particularly limited. From the viewpoint of the aggregation reaction efficiency of Ce and Zr (and other metal elements when included) (therefore, further reduction of crystallite diameter and further increase of BET specific surface area), it is preferably above 10 minutes and below 5 hours, and more preferably above 20 minutes and below 2 hours. It should be noted that the surface stabilization treatment can be carried out in any atmosphere such as air, oxygen, a mixed gas of oxygen and an inert gas (such as nitrogen, argon). It should be noted that the heat treatment temperatures in the solvent thermal treatment of step (II) and the surface stabilization treatment of step (III) overlap, but the solvent thermal treatment is carried out under pressure, while the surface stabilization treatment is carried out under normal pressure, so these treatments are different.
[0067] Here, the BET specific surface area of the precursor after surface stabilization treatment is preferably 155 m2 / g or more, more preferably 160m 2 / g or more, particularly preferably 170m 2 / g or more. If the BET specific surface area after surface stabilization treatment is within the above range, a high BET specific surface area can be maintained even after structural stabilization treatment, so it is preferred. It should be noted that the higher the BET specific surface area of the precursor after surface stabilization treatment, the more preferred it is. Therefore, the upper limit is not particularly limited, and is usually 350m 2 / g or less, preferably 300m 2 / g or less, more preferably 250m 2 / g or less.
[0068] (Step (IV))
[0069] The precursor obtained in the above step (III) is subjected to a structural stabilization treatment at a temperature above 380°C. The structural stabilization treatment is performed to enhance the structural stability of the Ce-Zr composite oxide whose surface is stabilized by oxides obtained by the surface stabilization treatment. By performing the structural stabilization treatment, the organic components originating from the raw materials remaining in the Ce-Zr composite oxide are burned and removed, promoting the solid solution of CeO2 and ZrO2, thereby enhancing the structural stability and being able to obtain a crystallite diameter of less than 6.5nm and a crystallite diameter of 90nm. 2 / g or more Ce-Zr composite oxide with a high BET specific surface area.
[0070] Here, if the temperature of the structure stabilization treatment is less than 380°C, part of the organic components derived from the raw materials will remain after the structure stabilization treatment, and therefore, the performance of the Ce-Zr composite oxide is reduced due to coking, etc., which is not preferred. From the viewpoints of the aggregation reaction efficiency of Ce and Zr (and other metal elements when included) (therefore, further reduction of the crystallite diameter and further increase of the BET specific surface area), removal of organic components, etc., the structure stabilization treatment temperature is preferably 380°C or more and less than 950°C, and more preferably 400°C or more and less than 800°C. In addition, the structure stabilization treatment time is not particularly limited, and from the viewpoints of the aggregation reaction efficiency of Ce and Zr (and other metal elements when included) (therefore, further reduction of the crystallite diameter and further increase of the BET specific surface area), removal of organic components, etc., it is preferably 15 minutes or more and 10 hours or less, more preferably 30 minutes or more and 5 hours or less, and even more preferably 1 hour or more and 3 hours or less.
[0071] It should be noted that the structural stabilization treatment may be performed in any atmosphere such as air, oxygen, or a mixed gas of oxygen and an inert gas (eg, nitrogen or argon).
[0072] The ratio of the BET specific surface area after the structure stabilization treatment of the Ce-Zr composite oxide of the present invention to the BET specific surface area after the surface stabilization treatment is preferably 0.54 or more and 1.0 or less, more preferably 0.8 or more and 0.98 or less, further preferably 0.9 or more and 0.95 or less, and particularly preferably 0.90 or more and 0.95 or less.
[0073] That is, in a preferred embodiment of the present invention, the BET specific surface area of the precursor obtained by surface stabilization treatment is 155 m 2 / g or more, and the ratio of the BET specific surface area of the Ce-Zr composite oxide after the structure stabilization treatment to the BET specific surface area of the precursor after the surface stabilization treatment is 0.54 or more and 1.0 or less. In a more preferred embodiment of the present invention, the BET specific surface area of the precursor obtained by the surface stabilization treatment is 160 m 2 / g or more, and the ratio of the BET specific surface area of the Ce-Zr composite oxide after the structural stabilization treatment to the BET specific surface area of the precursor after the surface stabilization treatment is 0.8 or more and 0.98 or less. In a particularly preferred embodiment of the present invention, the BET specific surface area of the precursor obtained by the surface stabilization treatment is 170 m 2 / g or more, and the ratio of the BET specific surface area of the Ce-Zr composite oxide after the structure stabilization treatment to the BET specific surface area of the precursor after the surface stabilization treatment is 0.9 to 0.95 (particularly 0.90 to 0.95).
[0074] In this specification, the BET specific surface area of the Ce-Zr composite oxide is a value measured by the BET method using nitrogen as an adsorbed molecule. Specifically, the BET specific surface area (m 2 / g).
[0075] The Ce-Zr composite oxide of the present invention is manufactured by the above method. The Ce-Zr composite oxide of the present invention has excellent oxygen storage and release characteristics even at low temperatures. Therefore, the Ce-Zr composite oxide of the present invention can be used as an oxygen storage material (OSC material) in an exhaust gas purification catalyst. That is, according to another embodiment of the present invention, a catalyst for exhaust gas purification is provided in which the Ce-Zr composite oxide of the present invention and a precious metal are supported on a three-dimensional structure. The above embodiment is described below. It should be noted that the catalyst for exhaust gas purification described in the above embodiment (hereinafter also referred to as "catalyst") is not limited except for including the Ce-Zr composite oxide of the present invention, and existing known components and technologies can be applied. Therefore, the present invention is not limited to the following contents.
[0076] The catalyst of the present invention must contain the Ce-Zr composite oxide of the present invention. Here, the content of the Ce-Zr composite oxide (supporting amount; oxide conversion) is not particularly limited, and is preferably 5 to 200 g, more preferably 5 to 100 g, and further preferably 10 to 90 g relative to 1 liter of the three-dimensional structure. By including the Ce-Zr composite oxide in such a content, the oxidation / reduction reaction can be stably performed.
[0077] (Precious Metals)
[0078] The catalyst described in the present invention must contain a precious metal (catalytic component). The precious metal (catalytic component) shows a catalytic effect in the oxidation / reduction reaction used to purify exhaust gas. Here, the type of precious metal is not particularly limited, and specifically, platinum (Pt), palladium (Pd), rhodium (Rh), etc. can be listed. These precious metals can be used alone or in combination of two or more. Among these, the precious metal is preferably platinum, palladium and rhodium, and more preferably palladium alone; a combination of platinum and / or palladium and rhodium, and particularly preferably palladium alone; a combination of palladium and rhodium. That is, according to a preferred form of the present invention, the precious metal is at least one selected from the group consisting of platinum, palladium and rhodium. In addition, according to a more preferred form of the present invention, the precious metal is only palladium, or at least one of platinum and palladium and rhodium. According to a particularly preferred form of the present invention, the precious metal is palladium, or palladium and rhodium.
[0079] Here, the amount of platinum (Pt) used (supporting amount) is not particularly limited. Considering the exhaust gas purification ability, it is preferably 0.01 to 20 g, more preferably 0.05 to 10 g, and most preferably more than 0.5 g and less than 5 g in terms of precious metal relative to 1 liter of the three-dimensional structure.
[0080] The amount of palladium (Pd) used (supported amount) is not particularly limited, but in consideration of the exhaust gas (especially HC) purification capability, it is preferably 0.01 to 20 g, more preferably 0.05 to 5 g, and most preferably 0.3 to 3 g in terms of precious metal relative to 1 liter of the three-dimensional structure.
[0081] The amount of rhodium (Rh) used (supported amount) is not particularly limited, but in consideration of the exhaust gas (especially NOx) purification capability, it is preferably 0.01 to 20 g, more preferably 0.05 to 5 g, and most preferably 0.1 to 3 g in terms of precious metal relative to 1 liter of the three-dimensional structure.
[0082] In addition, when the precious metals are platinum and palladium, the mixing ratio of platinum to palladium (platinum: palladium (mass ratio)) is preferably 50: 1 to 1: 1, 40: 1 to 1: 1, 30: 1 to 1.1: 1, 20: 1 to 1.3: 1, and 5: 1 to 1.5: 1. As the mixing ratio of platinum to palladium falls within the above preferred range, the exhaust gas purification efficiency can be improved.
[0083] When the precious metals are palladium and rhodium, the mixing ratio of palladium to rhodium (platinum: rhodium (mass ratio)) is preferably 30: 1 to 1.1: 1, more preferably 20: 1 to 1.3: 1, and particularly preferably 5: 1 to 1.5: 1. When the mixing ratio of palladium to rhodium falls within the above preferred range, the exhaust gas purification efficiency can be improved.
[0084] The noble metal source (starting material of the noble metal) is not particularly limited, and water-soluble noble metal salts, noble metal complexes and other raw materials used in this field can be used, and they can be used according to the method for preparing the catalyst. Specifically, as the raw material (palladium source) of palladium (Pd), halides such as palladium chloride can be listed; inorganic salts such as palladium nitrates, sulfates, acetates, ammonium salts, amine salts, tetraammine salts, hexaammine salts, carbonates, bicarbonates, nitrites, and oxalates; carboxylates such as formate; and hydroxides, alkoxides, oxides, etc. Among these, preferably nitrates (palladium nitrates), tetraammine salts (tetraammine palladium), hexaammine salts (hexaammine palladium), carboxylates, hydroxides, more preferably nitrates. It should be noted that in the present invention, the above-mentioned palladium source can be a single one, or it can also be a mixture of more than two kinds. As the raw material (rhodium source) of rhodium (Rh), inorganic salts such as ammonium salts, amine salts, hexaammine salts, carbonates, bicarbonates, nitrates, nitrites, and oxalates of rhodium can be listed; carboxylates such as formate; and hydroxides, alkoxides, oxides, etc. Among these, nitrates, ammonium salts, amine salts, hexaammine salts, and carbonates are preferred. It should be noted that in the present invention, the above-mentioned rhodium source can be a single species, or a mixture of two or more species. As the raw material (platinum source) of platinum (Pt), halides such as platinum bromide and platinum chloride can be listed; inorganic salts such as nitrates, dinitrodiammine salts, tetraammine salts, hexaammine salts, sulfates, ammonium salts, amine salts, diethanolamine salts, diacetylacetonate, carbonates, bicarbonates, nitrites, and oxalates of platinum; carboxylates such as formate; and hydroxides, alkoxides, hexahydroxy acid salts (hexahydroxo acid salts), oxides, etc. Among these, preferred are nitrates (platinum nitrate), dinitrodiammine salts (dinitrodiammine platinum), chlorides (platinum chloride), tetraammine salts (tetraammine platinum), hexaammine salts (hexaammine platinum), and hexahydroxy acid salts. It should be noted that in the present invention, the platinum source may be a single species or a mixture of two or more species.
[0085] The amount of the precious metal source is not particularly limited, and is preferably an amount that reaches the content (loaded amount) of each precious metal as described above. It should be noted that, when two or more precious metal sources are used in combination, it is preferred that the total amount of the precious metal sources reaches an amount that reaches the content (loaded amount) of the precious metal as described above.
[0086] (Refractory Inorganic Oxide)
[0087] The catalyst of the present invention may contain a refractory inorganic oxide in addition to or in place of the above-mentioned noble metal. The refractory inorganic oxide can be used as a carrier for catalytically active components such as noble metals, rare earth metals, and other metal elements. As a refractory inorganic oxide, there is no particular limitation as long as it is a substance used as a catalyst carrier. In addition, the refractory inorganic oxide has a high specific surface area, and by making it support the catalytic component, the contact area between the catalytic component and the exhaust gas can be increased, or the reactant can be adsorbed. As a result, the reactivity of the catalyst as a whole can be further improved.
[0088] As refractory inorganic oxides, for example, alumina, zeolite, titania, zirconia, silica, etc. can be cited. These refractory inorganic oxides can be used alone or in combination of two or more. Among these, from the viewpoint of high temperature durability and high specific surface area, alumina and zirconia are preferred, and alumina is more preferred. Here, the alumina preferably used as a refractory inorganic oxide is not particularly limited as long as it contains aluminum oxide, and examples include activated aluminas such as γ, δ, η, and θ-alumina; alumina containing lanthanum oxide, alumina containing silica, alumina containing silica-titania, alumina containing silica-titania-zirconium oxide, etc. These aluminas can be used alone or in combination of two or more. Among these, from the viewpoint of high temperature durability and high specific surface area, γ, δ or θ-alumina is preferred; alumina containing lanthanum oxide.
[0089] The BET specific surface area of the refractory inorganic oxide is not particularly limited, but is preferably 50 to 750 m 2 / g, more preferably 80 to 500 m 2 / g, particularly preferably 120 to 250 m 2 With such a specific surface area, a sufficient amount of precious metal (catalytic component) can be supported on the refractory inorganic oxide, which can increase the contact area between the catalytic component and the exhaust gas or adsorb reactants. As a result, the reactivity of the catalyst as a whole can be further improved.
[0090] The content (load) of the refractory inorganic oxide is not particularly limited, and is preferably 10 to 300 g, more preferably 30 to 200 g, relative to 1L of the three-dimensional structure. If the content of the refractory inorganic oxide per 1L of the three-dimensional structure is 10 g or more, the precious metal can be fully dispersed in the refractory inorganic oxide, and a catalyst with more sufficient durability can be obtained. On the other hand, if the content of the refractory inorganic oxide is 300 g or less relative to 1L of the three-dimensional structure, the contact state between the precious metal and the exhaust gas becomes good, and the exhaust gas purification performance can be more fully exerted. In addition, when the catalyst described in the present invention comprises the Ce-Zr composite oxide and the refractory inorganic oxide described in the present invention, the mixing ratio (mass ratio) of the Ce-Zr composite oxide and the refractory inorganic oxide is preferably 1:0.2 to 9, more preferably 1:0.8 to 5. If the ratio is such, a sufficient amount of precious metal (catalytic component) can be carried on the refractory inorganic oxide, the contact area between the catalytic component and the exhaust gas can be increased, and the Ce-Zr composite oxide can fully exert the oxygen storage and release characteristics, and can fully adsorb hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx) in the exhaust gas. As a result, the reactivity of the catalyst as a whole can be further improved, and the purification performance of the exhaust gas can be further improved.
[0091] (Rare Earth Elements)
[0092] The catalyst of the present invention may further include rare earth metals in addition to Ce-Zr composite oxides. Here, as rare earth metals, there is no particular limitation, and lanthanum (La), neodymium (Nd), yttrium (Y), scandium (Sc) and praseodymium (Pr) etc. can be listed. Among these, lanthanum, neodymium, yttrium and praseodymium are preferred, and lanthanum and praseodymium are more preferred. These rare earth metals may be contained alone or in combination of two or more. In addition, the rare earth metal may be in the form of the metal itself or in the form of an oxide.
[0093] The content of the rare earth metal (in terms of oxide) is preferably 0.2 to 30 g, more preferably 0.3 to 10 g, based on 1 liter of the three-dimensional structure.
[0094] (Other ingredients)
[0095] The catalyst of the present invention may further include other components. Here, other components are not particularly limited, and second group elements such as magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba) can be used. These elements can be contained in the exhaust gas purification catalyst in the form of oxides, sulfates, or carbonates. Among them, Ba and Sr are preferably used, and strontium oxide, barium sulfate (BaSO4) or barium oxide (BaO) is more preferably used. These other components can be used alone or in combination of two or more.
[0096] When the catalyst described in the present invention contains other components, the content (in terms of oxides) of the other components (especially SrO, BaSO4, BaO) is preferably 0 to 50 g, more preferably 0.1 to 30 g, and further preferably 0.5 to 20 g relative to 1 liter of the three-dimensional structure.
[0097] (Three-dimensional structure)
[0098] The catalyst of the present invention is a three-dimensional structure in which a noble metal and the Ce-Zr composite oxide of the present invention are supported.
[0099] Here, the three-dimensional structure is not particularly limited, and the refractory three-dimensional structure commonly used in the field can be used in the same manner. As the three-dimensional structure, heat-resistant carriers such as honeycomb carriers with triangular, quadrilateral, and hexagonal through-holes (gas passages, cell shapes) can be used. The three-dimensional structure is preferably an integrally formed structure (three-dimensional structure, integral weir structure), preferably using, for example, a monolithic carrier, a metal honeycomb carrier, a punching metal, etc.
[0100] These monolithic carriers are manufactured by extrusion molding, curling and fixing sheet elements, etc. The shape of the through-holes (gas vents, cell shape) can be any of hexagonal (honeycomb), quadrilateral, triangular or corrugated (wave-shaped). As long as the cell density (number of cells / unit cross-sectional area) is 100 to 1200 cells / square inch, it can be fully used, preferably 200 to 900 cells / square inch, more preferably 200 to 600 cells / square inch, and further preferably 250 to 500 cells / square inch (1 inch = 25.4 mm).
[0101] Preferred embodiments of the method for producing the catalyst of the present invention are described below, but the present invention is not limited to the preferred embodiments described below.
[0102] That is, the Ce-Zr composite oxide, the noble metal source, and other components as described above as needed (e.g., refractory inorganic oxides, rare earth metals, other components) and the aqueous medium described in the present invention are appropriately weighed and mixed according to the desired composition, stirred at 5 to 95° C. for 0.5 to 24 hours (wet crushed after stirring as needed) to prepare a slurry. Here, as the aqueous medium, water (pure water, ultrapure water, deionized water, distilled water, etc.), lower alcohols such as ethanol and 2-propanol, organic alkaline aqueous solutions, etc. can be used. Among them, water and lower alcohols are preferably used, and water is more preferably used. The amount of the aqueous medium is not particularly limited, and it is preferably an amount such that the proportion of the solid content in the slurry (solid content mass concentration) reaches 5 to 60% by mass, and more preferably reaches 10 to 50% by mass. The solid content ratio can be calculated from the following ratio: the mass of the solid content remaining after the above slurry is placed in a crucible and the solvent component is removed at 550°C in air for 30 minutes, relative to the mass of the slurry before the solvent component is removed at 550°C in air for 30 minutes.
[0103] Here, the order of addition of Ce-Zr composite oxide, noble metal source, and other raw materials (e.g., refractory inorganic oxide, rare earth metal, and other components) is not particularly limited, and they can be put into the aqueous medium together, or they can be added separately in an appropriate order. In addition, the pH of the mixture (slurry) after adding each raw material is preferably adjusted to 1 to 12, preferably to 3 to 9. Therefore, when the pH of the mixture (slurry) after each addition step deviates from the above range, it is preferred to use an acid such as hydrochloric acid, sulfuric acid, nitric acid, and carbonic acid, or an alkali such as ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate to adjust the pH to the above specified range.
[0104] Next, the slurry prepared as above is applied to the three-dimensional structure. The method for applying the slurry to the three-dimensional structure can appropriately adopt a known method such as a wash coat method. In addition, those skilled in the art can appropriately determine the amount of slurry applied based on the amount of solid matter in the slurry and the thickness of the catalyst layer formed. The amount of slurry applied is preferably an amount such that each component reaches the above-mentioned content (loaded amount).
[0105] Next, the three-dimensional structure coated with the slurry is preferably dried in the air at a temperature of 50 to 170°C, more preferably at a temperature of 70 to 150°C, for 5 minutes to 10 hours, preferably for 15 minutes to 3 hours. Next, the dried slurry coating (catalyst precursor layer) obtained by the above operation is calcined in the air at a temperature of 440°C to 800°C, preferably at a temperature of 450°C to 610°C, more preferably at a temperature of 450°C to 555°C for 10 minutes to 3 hours, preferably for 15 minutes to 1 hour. If it is such a condition, the catalyst components (precious metals, Ce-Zr composite oxides, etc.) can be efficiently attached (supported on) the three-dimensional structure. In addition, the calcining process is preferably carried out while circulating a gas such as air. Here, the gas circulation velocity (gas flow rate) is not particularly limited, preferably 0.1m / second or more, more preferably 0.2 to 1.2m / second. It should be noted that the above-mentioned catalyst layer forming step may be performed once, or may be performed multiple times (it is also possible to form two or more catalyst layers in the three-dimensional structure).
[0106] Through the above operation, the catalyst of the present invention can be manufactured. It should be noted that, as described above, the catalyst of the present invention may have only one catalyst layer as long as it has the Ce-Zr composite oxide of the present invention, or it may have a structure in which more than two catalyst layers are stacked. When the catalyst of the present invention has a structure in which more than two catalyst layers are stacked, the Ce-Zr composite oxide of the present invention may be configured in any catalyst layer. Preferably, the Ce-Zr composite oxide of the present invention is preferably configured in at least a layer containing palladium. Through this configuration, the ability of the Ce-Zr composite oxide of the present invention can be maximized. In addition, other catalyst layers that do not contain the Ce-Zr composite oxide of the present invention are not particularly limited and may be catalyst layers known in the field of catalysts. For example, the same composition (components) as above may be used except that the Ce-Zr composite oxide of the present invention is not used. In addition, the composition (components) in each catalyst layer may be the same or may be different. For example, among the precious metals, the preferred combination of precious metals in the two catalyst layers (recorded as a combination of precious metals in the catalyst lower layer and precious metals in the catalyst upper layer) is not limited to the following combinations, and there are combinations of platinum and rhodium, combinations of palladium and rhodium, combinations of platinum, palladium and rhodium, combinations of platinum, rhodium and palladium, combinations of palladium, rhodium and platinum, etc. Through this combination, the exhaust gas can be efficiently purified. Among them, the combination of platinum and rhodium, and the combination of palladium and rhodium are more preferred. It should be noted that it is not necessary to include precious metals in all catalyst layers, but it is preferred to include precious metals in all catalyst layers. As a result, the catalytic performance can be further improved.
[0107] <Exhaust gas purification method>
[0108] The catalyst of the present invention can exert high purification performance on exhaust gas (hydrocarbons (HC), carbon monoxide (CO), nitrogen oxides (NOx)) even at low temperatures. Therefore, the present invention also provides a method for purifying exhaust gas, which has the following steps: using the exhaust gas purification catalyst described in the present invention to treat the exhaust gas (especially purifying hydrocarbons (HC), carbon monoxide (CO) and nitrogen oxides (NOx) in the exhaust gas). It should be noted that the catalyst described in the present invention can be applied to exhaust gases from both gasoline engines and diesel engines, but can be particularly suitable for exhaust gases from gasoline engines. It should be noted that a gasoline engine can be used to evaluate the purification rate (purification capacity) of the exhaust gas based on the temperature (T50 (℃)) at which the purification rates of CO, THC, and NOx reach 50% in, for example, the following ignition (light-off, LO) test. It should be noted that the lower the T50, the higher the exhaust gas purification performance of the catalyst.
[0109] Exhaust gas usually contains HC, CO, NOx, and contains, for example, nitrogen oxides (such as NO, NO2, N2O), carbon monoxide (CO), carbon dioxide (CO2), oxygen (O2), hydrogen (H2), ammonia (NH3), water (H2O), sulfur dioxide (SO2), hydrocarbons (HC), etc. in any proportion.
[0110] The gasoline engine to which the exhaust gas purification method of this form is applied intends to emphasize its difference from the diesel engine, and includes, in addition to the ordinary gasoline engine, for example, a gasoline hybrid engine, an engine using natural gas, ethanol, dimethyl ether, etc. as fuel, etc. Among them, the gasoline engine is preferred.
[0111] Examples of a method for making the exhaust gas contact the catalyst of the present invention include a method in which, for example, the exhaust gas-purifying catalyst is disposed in an exhaust flow path of an exhaust port of a gasoline engine and the exhaust gas is allowed to flow into the exhaust flow path.
[0112] The catalyst of the present invention can exert high exhaust gas purification performance even in a low temperature region, but the exhaust gas temperature can be 0°C to 800°C, in other words, within the exhaust gas temperature range when a normal gasoline engine is running. Here, the air-fuel ratio (A / F) in the exhaust gas of a gasoline engine at a temperature of 0°C to 800°C is 10 to 30, preferably 11.0 to 14.7.
[0113] Examples of a method for making the exhaust gas contact the catalyst of the present invention include a method in which, for example, the exhaust gas-purifying catalyst is disposed in an exhaust flow path of an exhaust port of a gasoline engine and the exhaust gas is allowed to flow into the exhaust flow path.
[0114] The catalyst of the present invention can exert high exhaust gas purification performance even in low temperature regions. In detail, the catalyst of the present invention can also exert excellent exhaust gas treatment effects for low temperature exhaust gas (especially containing HC, CO, NOx, water vapor, etc.) of 50 to 600°C (especially 100 to 500°C), or for high temperature exhaust gas (especially containing HC, CO, NOx, water vapor, etc.) of 650 to 900°C in the catalyst bed. The catalyst of the present invention can also exert high purification performance even in the high temperature region of 800 to 1200°C on the basis of the above-mentioned low temperature region. Here, the air-fuel ratio of the exhaust gas of the internal combustion engine with a temperature of 800 to 1200°C is preferably 10 to 18.6.
[0115] Therefore, the catalyst of the present invention as described above or the catalyst produced by the method as described above can be exposed to exhaust gas at a temperature of 800 to 1200°C, preferably 900 to 1000°C. In addition, the time for which the catalyst of the present invention is exposed to high-temperature exhaust gas (the time for which the exhaust gas is allowed to flow in) is not particularly limited, and is, for example, 10 to 800 hours, preferably 16 to 500 hours, and more preferably 40 to 100 hours. After exposure to such high-temperature exhaust gas, the catalyst of the present invention also has high performance. In order to investigate the exhaust gas purification performance of the catalyst after exposure to high-temperature exhaust gas like this, it is effective to evaluate the exhaust gas purification performance (tolerance to catalyst degradation) after subjecting the catalyst to a treatment as a heat treatment in which the catalyst is exposed to exhaust gas at 900 to 1000°C for 10 to 300 hours.
[0116] It should be noted that, in this specification, "the temperature of the exhaust gas" refers to the exhaust gas temperature at the catalyst inlet. Here, the "catalyst inlet" refers to the portion from the catalyst end face on the exhaust gas inlet side of the exhaust pipe provided with the exhaust gas purification catalyst toward the internal combustion engine side to 10 cm, and refers to the center portion of the exhaust pipe in the length direction (axial direction). In addition, in this specification, the "catalyst bed" refers to the central portion from the catalyst end face on the exhaust gas inlet side of the above-mentioned exhaust pipe to the catalyst end face on the exhaust gas outflow side, and the center portion of the cross section of the exhaust pipe (when the cross section of the exhaust pipe is not circular, it is the center of gravity of the cross section of the exhaust pipe).
[0117] In addition, the catalyst of this form can exert sufficient catalytic activity alone, and the same or different exhaust gas purification catalysts can also be configured in the front section (inflow side) or the rear section (outflow side) of the catalyst described in the present invention. It is preferred to configure the catalyst described in the present invention alone, or to configure the catalyst described in the present invention in both the front section (inflow side) and the rear section (outflow side), or to configure the catalyst of the present invention in either the front section (inflow side) and the rear section (outflow side) and configure the existing known exhaust gas purification catalyst in the other. It is more preferred to configure the catalyst of the present invention alone, or to configure the catalyst of the present invention in both the front section (inflow side) and the rear section (outflow side).
[0118] Example
[0119] The present invention is described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples. It should be noted that, unless otherwise specified, each operation is performed under the conditions of room temperature (25° C.) / relative humidity of 40 to 50% RH. In addition, unless otherwise specified, the ratio represents a mass ratio.
[0120] [Example 1]
[0121] Cerium acetate 1.5 hydrate was used as a Ce raw material, zirconium tetra-n-propoxide was used as a Zr raw material, and lanthanum acetylacetonate dihydrate was used as a La raw material, and the composition ratio (mass ratio) of CeO2:ZrO2:La2O3 was weighed in such a way that the value in Table 1 was obtained. Each raw material was added to a container weighing 400 mL of 1,4-butanediol as a solvent, and stirred for 10 minutes using a Three-One Motor to obtain a mixture (solid content concentration = 1.5 g / 100 mL 1,4-butanediol). The mixture was transferred to an autoclave (manufactured by Nitto High Pressure Co., Ltd., trade name: NU-4), and the obtained mixture was stirred at 340°C for 2 hours in an autoclave substituted with N2 (reaction pressure = 10.3 MPa) (solvent heat treatment). The obtained product was separated by a centrifuge, and a surface stabilization treatment was performed in air at 250°C for 30 minutes to obtain a precursor A'. The BET specific surface area of the precursor A' obtained here was measured. In addition, in the measurement of BET specific surface area, TriStarII3020 manufactured by Micromeritics was used. The results are shown in "BET specific surface area (after surface stabilization treatment)" in Table 2 below.
[0122] Next, the obtained precursor A' was subjected to a structural stabilization treatment at 500°C in air for 1 hour, thereby obtaining a powder A. The powder H thus obtained was a Ce-Zr-La composite oxide containing cerium, zirconium and lanthanum in a ratio of 47:47:6 (mass ratio of CeO2:ZrO2:La2O3) [Ce:Zr:La (atomic ratio) = 40:57:3].
[0123] [Example 2]
[0124] In Example 1, the powder B was obtained by the same operation as in Example 1 except that the mixture was stirred at 300° C. for 2 hours in an autoclave replaced with N2 (solvent thermal treatment). It should be noted that in this example, the BET specific surface area of the precursor (precursor B') after the surface stabilization treatment was measured in the same manner as in Example 1, and the results are shown in the "BET specific surface area (after surface stabilization treatment)" in the following Table 2.
[0125] [Comparative Example 1]
[0126] In Example 1, the powder C was obtained by the same operation as in Example 1 except that the mixture was stirred at 250° C. for 2 hours in an autoclave replaced with N2 (solvent thermal treatment). It should be noted that in this example, the BET specific surface area of the precursor (precursor C') after the surface stabilization treatment was measured in the same manner as in Example 1, and the results are shown in the "BET specific surface area (after surface stabilization treatment)" in the following Table 2.
[0127] [Example 3]
[0128] In Example 1, except that zirconium acetylacetonate was used as the Zr raw material, the same operation as in Example 1 was performed to obtain powder D. It should be noted that in this example, the BET specific surface area of the precursor (precursor D') after the surface stabilization treatment was measured in the same manner as in Example 1, and the results are shown in the "BET specific surface area (after surface stabilization treatment)" in the following Table 2.
[0129] [Comparative Example 2]
[0130] In Example 3, the powder E was obtained by the same operation as in Example 3 except that the mixture was stirred at 200° C. for 2 hours in an autoclave replaced with N2 (solvent thermal treatment). It should be noted that in this example, the BET specific surface area of the precursor (precursor E') after the surface stabilization treatment was measured in the same manner as in Example 1, and the results are shown in the "BET specific surface area (after surface stabilization treatment)" in the following Table 2.
[0131] [Example 4]
[0132] In Example 3, except that triacetylacetonate cerium (III) dihydrate was used as the Ce raw material, the same operation as in Example 3 was performed to obtain powder F. It should be noted that in this example, the BET specific surface area of the precursor (precursor F') after surface stabilization treatment was measured in the same manner as in Example 1, and the results are shown in the "BET specific surface area (after surface stabilization treatment)" in the following Table 2.
[0133] [Comparative Example 3]
[0134] Cerium nitrate was used as a Ce raw material, zirconium nitrate was used as a Zr raw material, and lanthanum nitrate was used as a La raw material, and they were weighed respectively in such a way that the composition ratio (mass ratio) of CeO2:ZrO2:La2O3 became the value of Table 1. Each raw material was put into a container weighed with 500 mL of distilled water, and stirred for 10 minutes using a Three-One Motor. Ammonia was added to the stirred solution in such a way that the pH reached 10, so that cerium hydroxide, zirconium hydroxide and lanthanum hydroxide were co-precipitated. Using a centrifuge, the resulting product was centrifuged at 3500 rpm for 10 minutes. After removing the supernatant, water was added to wash the product, and centrifuged at 3500 rpm for 10 minutes. The above-mentioned washing and centrifugal separation operations were repeated a total of 3 times to obtain the product. The resulting product was dried in air at 250°C for 30 minutes, and then subjected to a structural stabilization treatment in air at 500°C for 1 hour, thereby obtaining powder G.
[0135] [Table 1]
[0136] Table 1 Composition ratio of each powder after structure stabilization treatment [mass %]
[0137] Powder <![CDATA[CeO2]]> <![CDATA[ZrO2]]> <![CDATA[La2O3]]> A 47 47 6 B 47 47 6 C 47 47 6 D 47 47 6 E 47 47 6 F 47 47 6 G 47 47 6 H 30 64 6 I 30 64 6 J 64 30 6 K 64 30 6
[0138] The BET specific surface area of the powders A to G obtained above was measured. It should be noted that the BET specific surface area was measured using TriStar I13020 manufactured by Micromeritics. The results are shown in the "BET specific surface area (after structural stabilization treatment)" and " Figure 1 From Table 2 and Figure 1 It can be seen that the BET specific surface area of powders A, B, D and F with a synthesis (solvent thermal treatment) temperature higher than 250°C is greater than that of powder C (solvent thermal method with a synthesis temperature of 250°C), powder E (solvent thermal method with a synthesis temperature of 200°C) and powder G (co-precipitation method) of the comparative example.
[0139] [Example 5]
[0140] In Example 3, the powders were weighed in such a manner that the composition ratio (mass ratio) of CeO2:ZrO2:La2O3 became the value in Table 1, and the same operation as in Example 3 was performed to obtain powder H. Powder H obtained in this way is a Ce-Zr-La composite oxide containing cerium, zirconium and lanthanum in a ratio of 30:64:6 (mass ratio of CeO2:ZrO2:La2O3) [Ce:Zr:La (atomic ratio) = 24:73:3].
[0141] [Comparative Example 4]
[0142] In Comparative Example 3, the powder I was obtained in the same manner as in Comparative Example 3, except that the compositions (mass ratio) of CeO 2 :ZrO 2 :La 2 O 3 were weighed so as to have the values shown in Table 1.
[0143] The BET specific surface area of the powders H and I obtained above was measured in the same manner as above. The results are shown in the "BET specific surface area (after structural stabilization treatment)" and " Figure 2 .Depend on Figure 2 It is found that the powder H produced by the solvothermal method has a larger BET specific surface area than the powder I produced by the coprecipitation method.
[0144] [Example 6]
[0145] In Example 3, the compositions of CeO2:ZrO2:La2O3 were weighed in such a manner that the composition ratio (mass ratio) of CeO2:ZrO2:La2O3 became the value in Table 1. The same operation as in Example 3 was performed to obtain a powder J. The powder J thus obtained was a Ce-Zr-La composite oxide containing cerium, zirconium and lanthanum in a ratio of 64:30:6 (mass ratio of CeO2:ZrO2:La2O3) [Ce:Zr:La (atomic ratio) = 59:38:3].
[0146] [Comparative Example 5]
[0147] In Comparative Example 3, except that the components were weighed so that the composition ratio (mass ratio) of CeO 2 :ZrO 2 :La 2 O 3 became the value in Table 1, the same operation as in Comparative Example 3 was carried out to obtain a powder K.
[0148] The BET specific surface area of the powders J and K obtained above was measured in the same manner as above. The results are shown in the "BET specific surface area (after structural stabilization treatment)" and " Figure 3 .Depend on Figure 3 It is found that the powder J produced by the solvothermal method has a larger BET specific surface area than the powder K produced by the coprecipitation method.
[0149] In addition, XRD measurement was performed on each powder A to K to measure the crystallite diameter (nm). The measurement was performed using X'Pert Pro manufactured by Spectris Corporation, and a copper tube was used for the X-ray tube. The X-ray wavelength λ is K was 0.9. In addition, the R value was calculated from the obtained crystallite diameter. The results are shown in Table 2 below.
[0150] [Table 2]
[0151]
[0152] Furthermore, H2-TPR measurement was performed on powders A, D, G, H, I and K. The fully automatic catalyst gas adsorption measuring device "R-6015" (manufactured by HEMMI Slide Rule Co., Ltd.) was used in the measurement. Specifically, 0.5 g of each powder was subjected to oxidation treatment at 500°C for 10 minutes under the circulation of oxygen (O2), and then the temperature was lowered to room temperature (25°C), and helium (He) was circulated for 15 minutes to fully purge excess O2 remaining in the device. Thereafter, the circulation condition was switched to He containing 5% H2, and the temperature was raised to 700°C. The generation behavior of H2O during the temperature rise was continuously measured using a TCD (thermal conductivity detector). Based on the obtained H2O generation curve, the temperature at which the most H2O is generated is calculated as the H2O generation peak temperature ( Figure 4 The peak temperature in H2-TPR measurement (°C) relative to the R value of each powder is calculated. Figure 4 The relationship between the peak temperature in TPR (°C) and the peak temperature in TPR (°C) is shown in Figure 4 .
[0153] [Example 7]
[0154] Palladium nitrate as a Pd raw material, the powder A obtained in Example 1, and alumina (average secondary particle size: 25 μm, BET specific surface area: 150 m 2 / g), strontium hydroxide, and lanthanum acetate. A specified amount of palladium nitrate, powder A, aluminum oxide, strontium hydroxide, and lanthanum acetate were added to 300 mL of distilled water and stirred for 1 hour using a Three-One Motor. After adjusting the pH to 6 with nitric acid, wet grinding was performed using a ball mill to obtain a slurry (solid content mass concentration = 40% by mass). At this time, the particle size (D50) of the slurry was 5 μm. Next, the resulting slurry was primed on a cordierite carrier (cylindrical with a diameter of 24 mm and a length of 67 mm, 400 cells / 1 square inch, and a wall pressure of 2.5 mils) in such a manner that the mass after sintering reached 112 g relative to 1 liter of the three-dimensional structure. Next, after drying in air at 150°C for 1 hour, it was sintered in air at 550°C for 30 minutes to obtain catalyst M.
[0155] [Comparative Example 6]
[0156] Catalyst N was obtained in the same manner as in Example 7 except that powder G was used instead of powder A.
[0157] The exhaust gas purification performance of the exhaust gas-purifying catalysts M and N produced as described above was evaluated by the following method.
[0158] <Heat resistance treatment>
[0159] Each exhaust gas purification catalyst was set at a position 25 cm downstream from the exhaust port of a V-type eight-cylinder, 4.6-liter gasoline engine. The engine was operated so that the temperature of the catalyst bed reached 960°C, and the engine was operated so that the A / F at the catalyst inlet reached 14.6. Then, the fuel supply was stopped so that the A / F reached 13.0, and this cycle was repeated. Through this cycle, the heat resistance treatment of each exhaust gas purification catalyst was performed for a total of 50 hours.
[0160] <Exhaust gas purification performance evaluation>
[0161] The exhaust gas purification catalysts after the heat-resistant treatment were respectively set at a position 30 cm downstream from the exhaust port of a straight six-cylinder, 2.4-liter gasoline engine. The engine was operated in such a way that the A / F at the catalyst inlet reached 14.6, and the temperature of the catalyst inlet was raised from 100°C to 500°C at a rate of 50°C per minute while the exhaust gas was circulated in the catalyst. The gas discharged from the catalyst outlet was analyzed, and the purification rates of CO, HC and NOx were calculated. The temperature at which each purification rate reached 50% was set as T50.
[0162] The results are shown in Figure 5 . Figure 5 It is shown that the catalyst M of the example is superior to the catalyst N of the comparative example in purification performance of CO, HC, and NOx.
[0163] This application is based on Japanese Patent Application No. 2020-078886 filed on April 28, 2020, the disclosed contents of which are incorporated herein by reference in their entirety.
Claims
1. A Ce-Zr composite oxide having a crystallite diameter of less than 6.5 nm and a BET specific surface area of 135 m 2 / g or above, The Ce-Zr composite oxide is composed of at least one selected from cerium and ceria, at least one selected from zirconium and zirconium oxide, and at least one metal selected from the group consisting of neodymium, lanthanum, praseodymium, and yttrium, or oxides of the metals. 2 . The Ce-Zr composite oxide according to claim 1 , wherein the R value is 1.5 or more.
3. A method for producing a Ce-Zr composite oxide, comprising the following steps: mixing a cerium compound and a zirconium compound to obtain a mixture; The mixture is subjected to a solvothermal treatment at a temperature exceeding 250° C. to obtain a solvothermal treatment product; The solvent thermal treatment product is subjected to a surface stabilization treatment at a temperature of 220° C. or higher and lower than 380° C. to obtain a precursor; The precursor is subjected to a structural stabilization treatment at a temperature of 380° C. or higher to generate a Ce-Zr composite oxide. The BET specific surface area of the precursor obtained by the surface stabilization treatment was 155 m 2 / g or more, and a ratio of a BET specific surface area of the Ce-Zr composite oxide after the structure stabilization treatment to a BET specific surface area of the precursor after the surface stabilization treatment is 0.54 or more and 1.0 or less.
4. The method according to claim 3, wherein: The solvothermal treatment is performed in a closed system replaced with an inert gas. 5 . An exhaust gas purification catalyst, wherein the Ce—Zr composite oxide according to claim 1 or 2 and a noble metal are supported on a three-dimensional structure.
6. A method for purifying waste gas, comprising the following steps: Exhaust gas is treated using the exhaust gas purification catalyst according to claim 5.
Citation Information
Patent Citations
Fine zirconia powder and its production
JP1998212122A
Mold device and method for manufacturing flow passage member
JP2020078886A
Ceria-zirconia solid solution crystal fine grain and process for producing the same
CN101896429A
Composite zirconium-cerium oxide, process for the preparation thereof, and cocatalyst for cleaning exhaust gas
CN1241988A
Production of fine powdery tetragonal zirconia of ceria solid solution
JP1992342421A